N-salicylidene-4-chloroaniline as protector material in preventing corrosion phenomenon in acidic medium / Nurul Amira Mohd Riffin... [et al.] - Mohd Riffin, Nurul Amira; Abdul Halim, Nurul Huda; Said, Nur Rahimah; Mohd Shotor, Siti Noriah (Universiti Teknologi MARA, Negeri Sembilan, 2017)
Corrosion inhibitor was used for protection of metals and alloys in dealing with corrosion problems. Recently, Schiff base ligands have been reported as effective corrosion inhibitors due to the presence of Nitrogen, Sulphur, Oxygen, C=N group, and π-bond that can form a covalent bond and help in reducing corrosion rate. This research introduces N-salicylidene-4- chloroaniline as a protector material in preventing corrosion phenomenon (corrosion inhibitor) in our surrounding. The structure of this compound was characterised using CHN elemental analysis, FTIR, 1 HNMR, and UV-Vis spectroscopy. The combination results proved that this compound has C=N group and π-bond, which are good inhibitor properties. The corrosion inhibitor study in 1 M HCl solution was conducted via weight loss method. Results showed that the increase of inhibitor concentration will increase the inhibition efficiency and vice versa to immersion time, where the inhibition efficiency decreases with a longer exposure of mild steel in acidic medium. The conducted experiment shows that the percentage of inhibition efficiency is 80.0% in 78 hours reaction. It showed that the ligand can act as a good corrosion inhibitor in 0.1 M concentration, which slows the corrosion rate on the metal surface.